Readings in economic development and administration in Tanzania - Smith, Hadley E. (London : Published for the Institute of Public Administration, University College, Dar es Salaam [by Oxford University Press, 1966)
This is a collection of readings that examines the Tanzanian economy prior to 1965.
Includes bibliographical references: p. [571]-595.
lje 25/01/2018
Loans
Keywords: Ecconomic development; Public administration; Tanzania